2010
DOI: 10.1111/j.1524-4725.2010.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Botulinum Toxin Type A Preparations for Treating Crow's Feet: A Split-Face, Double-Blind, Proof-of-Concept Study

Abstract: Both botulinum toxin A products displayed high efficacy and good tolerability at a dose ratio of 1:1, with no statistically significant differences between them. The high response rates observed after 4 months suggest a good effectiveness beyond this observation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 23 publications
(52 reference statements)
2
23
0
4
Order By: Relevance
“…In addition, the total dosages for both products were similar and low, as expected for cosmetic procedures in the face. Therefore, the results from this large retrospective study (n = 1256) are in line with published results of smaller prospective clinical studies which have shown similar efficacy of incobotulinumtoxinA compared with onabotulinumtoxinA in the treatment of glabellar frown lines in 381 subjects,7 crow’s feet in 21 subjects,6 and forehead lines in 12 subjects9 in aesthetic indications using identical dosages, as well as in therapeutic indications with similar dosages 10,11…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the total dosages for both products were similar and low, as expected for cosmetic procedures in the face. Therefore, the results from this large retrospective study (n = 1256) are in line with published results of smaller prospective clinical studies which have shown similar efficacy of incobotulinumtoxinA compared with onabotulinumtoxinA in the treatment of glabellar frown lines in 381 subjects,7 crow’s feet in 21 subjects,6 and forehead lines in 12 subjects9 in aesthetic indications using identical dosages, as well as in therapeutic indications with similar dosages 10,11…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, in a large head-to-head study comparing incobotulinumtoxinA with onabotulinumtoxinA for the treatment of glabellar frown lines, the percentage of responders 4 and 12 weeks after injection of the same number of units (U) of either preparation were similar, and demonstrated that both treatments were highly effective according to the assessment of independent raters, investigators, and subjects 7. No statistically significant difference in efficacy was observed in a proof-of-concept study in the treatment of crow’s feet6 and in the treatment of forehead lines9 using a 1:1 dose ratio of the two products.…”
Section: Introductionmentioning
confidence: 97%
“…The safety results show that incobotulinumtoxinA treatment was well tolerated, as reported previously,6,7,19 and no serious AEs – or any deemed to be related to the study drug – occurred.…”
Section: Discussionsupporting
confidence: 81%
“…Die Wirkungsdauer für die Behandlung von "Krähenfüßen" wird mit 3 Monaten angegeben [57], die der Stirnfalten mit 3-4 Monaten [79,80]. Vergleichsstudien der einzelnen Produkte haben bezüglich der Wirkungsdauer ebenso widersprüchliche Ergebnisse ergeben, so dass in diesem Zusammenhang zur genauen Klärung weitere prospektive Studien mit großen Fallzahlen notwendig sind [51,[80][81][82].…”
Section: Wirkungseintritt Und Wirkungsdauerunclassified